Diagnostics of the cardio-toxic effects of oncology therapies - Podoba, Roman; Lacko, Anton; Straka, Ján; Zachar, Lukáš (Journal of Nursing, Social Studies and Public Health, 2017)
Despite the rising trend of cancer disease incidence more and more patients succeed in their fight with the disease. Innovative drugs bring cures or at least improvements to the patient's quality of life. Extensive application of anticancer therapy however brings about the increase of adverse effects of the therapy. Toxic damage of the myocardium remains one of the severest organ damage types with life-threatening consequences. In the last decade, in addition to the known cardio toxicity of traditional cytostatics, specialists have more and more often been facing cardio toxicity caused by targeted oncology therapies. As myocardium damage is hard to treat when the stage of clinical symptoms is reached, emphasis is laid on the timely diagnosing of this drug-related damage. Diagnostic procedures have been introduced for early detection of risk patients before the therapy has even commenced. Timely diagnosis of myocardium effects in the course of the conservative cancer therapy allows for adjustment of the oncology therapy and lifestyle and timely commencement of treatment of the affected myocardium. Echocardiograph is considered the basic procedure of patient monitoring during cancer therapy. MRI of the myocardium and CT cardiograph are limited by price and availability despite their uncontentious role in oncocardiology. Radionuclide ventriculography is considered the gold standard of assessment of the left ventricle function. It is well reproducible and widely available in oncology centres. Laboratory diagnostics of toxic damage of the myocardium focuses on cardinal troponins and natriuretic peptides. This examination performance in clinical practice is undemanding and its application in oncology practice increases.
Keywords: bevacizumab; Magnetic Resonance Imaging; antracykliny; fluoruracil; Fluorouracil; echokardiografie; nemoci srdce; Electrocardiography; Sunitinib; lidé; radioisotopová ventrikulografie; Bevacizumab; trastuzumab; elektrokardiografie; cílená molekulární terapie; nádory; magnetická rezonanční tomografie; Risk Factors; 3-jodobenzylguanidin; Myocardium; jednofotonová emisní výpočetní tomografie; Antineoplastic Agents; Biological Therapy; Neoplasms; sunitinib; Molecular Targeted Therapy; Echocardiography; biologická terapie; Heart Diseases; Tomography, Emission-Computed, Single-Photon; rizikové faktory; Radionuclide Ventriculography; 3-Iodobenzylguanidine; myokard; Humans; Anthracyclines; protinádorové látky; Cardiotoxicity; kardiotoxicita; Trastuzumab